Relationship Between Distributive Justice And Organization Commitment: Job Satisfaction As Mediator Among Public Employees In Malaysia. - Nor Azima Ahmad; Umi Hamidaton Mohd Soffian Lee; Siti Salwa Salim (Human Resource Management Academic Research Society, 2024)
Indexed by ERA